2023
DOI: 10.3390/nu15030652
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Biomarkers as Predictors of Dysphonia Severity in Patients with Ischemic Stroke

Abstract: Dysphonia and malnutrition are major problems in patients who have suffered an ischemic stroke. Tools to assess dysphonia severity include the dysphonia severity index (DSI) and maximum phonation time (MPT). This study aimed to investigate whether the nutritional biomarkers transferrin, albumin, and prealbumin could be predictors of dysphonia severity. A retrospective analysis was conducted between January 2018 and October 2022. A total of 180 patients who had suffered an ischemic stroke were included. Serum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Together with malnutrition, dysphonia is a major problem in patients who have experienced an ischemic stroke. The study conducted by Kim and colleagues [2] found that serum levels of transferrin, albumin, and prealbumin were significantly correlated with the dysphonia severity index and maximum phonation time levels. In a multiple regression analysis, prealbumin and transferrin were found to be significant predictors of the dysphonia severity index, whereas prealbumin alone was a significant predictor of the maximum phonation time.…”
Section: Nutrition In Post-stroke Subjects During Rehabilitation Mari...mentioning
confidence: 97%
See 1 more Smart Citation
“…Together with malnutrition, dysphonia is a major problem in patients who have experienced an ischemic stroke. The study conducted by Kim and colleagues [2] found that serum levels of transferrin, albumin, and prealbumin were significantly correlated with the dysphonia severity index and maximum phonation time levels. In a multiple regression analysis, prealbumin and transferrin were found to be significant predictors of the dysphonia severity index, whereas prealbumin alone was a significant predictor of the maximum phonation time.…”
Section: Nutrition In Post-stroke Subjects During Rehabilitation Mari...mentioning
confidence: 97%
“…Two of three studies analyzed albumin, prealbumin, and transferrin as nutritional biomarkers in post-stroke patients. Park et al studied these nutritional biomarkers in association with heart rate variability [1], while Kim et al examined them as predictors of dysphonia severity [2].…”
Section: Nutrition In Post-stroke Subjects During Rehabilitation Mari...mentioning
confidence: 99%
“…On the other hand, prealbumin (PA), synthesized in the liver, plays a crucial role in blood transport [ 8 ]. With a shorter half-life compared to albumin, PA provides a rapid reflection of the patient's nutritional status [ 9 ]. Low PA levels indicate malnutrition and compromised liver function.…”
Section: Introductionmentioning
confidence: 99%